The A novel Artificial Neural Networks and FCNN algorithms for identifications of Fake Profiles (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Fake accounts in online networks are becoming more difficult to spot, and even the most fundamental tactics aren't always reliable. Consequently, I was prompted to create the suggested research using an Artificial Neural Networks (ANN) module from deep learning in order to identify if provided record peculiarities are from certified or counterfeit customers. According to previous customer records, this ANN will be computed based on that information from a given date. We'll create this ANN calculation using all of ourprevious customers' false profile data and verified record information, and we'll use it on all fresh test data to see whether the new record subtleties we get are from genuine or fraudulent clients. It is possible for malicious clients to hack into online interpersonal organisations, such as Facebook or Twitter, in order to steal or get access to a user's private information. Fake accounts on social media sites may be detected using an ANN model, which helps us protect our customers' data.